Kajian Mendalam Analisis Infak Produktif: Pendekatan Strategis Mewujudkan Maqasid Syariah - Arifin, Samsul; Herianingrum, Sri (Jurnal Ilmiah Ekonomi Islam, 2024)
Abstract Islam encourages social care through Zakat, Infaq and Shadaqah (ZIS). ZIS funds that are managed productively can create jobs, improve the economy and distribute welfare. Islam opposes hoarding wealth and prioritizes healthy economic circulation. Productive financial management, such as providing working capital, supporting MSMEs, and fulfilling sharia maqashid, can improve welfare. Managing ZIS evenly and stimulating independence leads to a more even distribution of income. Islam emphasizes the positive contribution of Islamic-based institutions to fulfilling basic needs. Keywords : ZIS, Economic Productivity, Maqashid Syariah, Welfare, Infaq